2015
DOI: 10.1007/s13277-015-4161-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from adriamycin-resistant breast cancer cells transmit drug resistance partly by delivering miR-222

Abstract: Breast cancer (BCa) is one of the major deadly cancers in women. However, treatment of BCa is still hindered by the acquired-drug resistance. It is increasingly reported that exosomes take part in the development, metastasis, and drug resistance of BCa. However, the specific role of exosomes in drug resistance of BCa is poorly understood. In this study, we investigate whether exosomes transmit drug resistance through delivering miR-222. We established an adriamycin-resistant variant of Michigan Cancer Foundati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 23 publications
1
63
0
Order By: Relevance
“…For example, Shanliang Zhong et al [20] found in breast cancer that a number of miRNAs were concentrated in exosomes and participate in the process of drug resistance. Yu DD et al [21] demonstrated that exosomes can effectively transmitted drug resistance in breast cancer, and the delivery of miR-222 via exosomes can serve as the mechanism. However, there is little research on the role of exosomal miRNAs in the process of lung cancer cells to cisplatin(DDP) resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shanliang Zhong et al [20] found in breast cancer that a number of miRNAs were concentrated in exosomes and participate in the process of drug resistance. Yu DD et al [21] demonstrated that exosomes can effectively transmitted drug resistance in breast cancer, and the delivery of miR-222 via exosomes can serve as the mechanism. However, there is little research on the role of exosomal miRNAs in the process of lung cancer cells to cisplatin(DDP) resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have identified a close association between exosomes and drug resistance in various types of cancer, including breast (9,22), ovarian (23) and prostate (24) cancer, which suggests that drug resistance in lung cancer cells may be acquired via exosomes. Cisplatin exposure may increase exosome secretion and the interaction of these secreted exosomes with other cancer cells may increase the resistance of A549 cells to cisplatin (10).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, melanoma-derived exosomes have been shown to transfer the C-Met oncoprotein to bone marrow progenitor cells, inducing vascular leakiness at pre-metastatic sites, and promoting metastasis in mouse tumor models [54]. They also appear to influence drug resistance; for instance, exosomes isolated from an adriamycin-resistant breast cancer cell lines have been found to transfer drug resistance to drug-sensitive human breast cancer cell lines upon delivery of miR-222 in vitro [55]. An association between exosomes and obesity-related insulin resistance has also been reported; in this study, adipocyte-derived exosomes were found to activate adipose-resident macrophages and secrete inflammatory cytokines (L-6 and TNF-alpha), leading to insulin resistance in a ob/ob obesity mouse model [56].…”
Section: Strategies For Therapeutic Deployment Of Exosomesmentioning
confidence: 99%